The history of negation in the languages of Europe and the Mediterranean - Willis, David W. E (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; Comparing Diachronies of Negation -- Negation in the History of French -- Negation in the History of Italo-Romance -- Negation in the History of English -- Negation in the History of High German -- Negation in the History of Low German and Dutch -- Negation in the History of the Brythonic Celtic Languages -- Negation in the History of Greek -- Negation in the History of the Slavonic Languages -- Negation in the History of Arabic and Afro-Asiatic -- Negation in the History of the Mordvin Languages